How PBL can increase the efficiency of educational process at law school? - Țurcan, Liliana; Zamfir, Natalia; Vidaicu, Mihaela (Tipografia Sinectica-Com SRL, 2017)
This articles aims at providing the approach towards problem based learning at Moldova law schools. Taking into account that current law schools’ curriculum contains several elements of problem based learning, authors of this article provided examples of specific interventions used in teaching several braches of law. In particular, authors described the use of individual research projects for administrative law, a group project for constitutional law and solving a practical issue for environmental law. Authors emphasized the need for problem based approach for other branches of law as well taking into account the specifics of legal studies and the need for including skills based courses in the university curriculum. Moreover, authors came up with a list of recommendations to facilitate introducing of the problem based learning at law schools.
Keywords: law school; students’ learning; individual research project; braches of law; administrative law; constitutional law; environmental law